The changing role of economic evaluation in valuing medical technologies. (December 2012) - Rotter, Jason S; Foerster, Douglas; Bridges, John FP
Economic evaluation is established within health-technology assessment but is challenged by those wanting to use economic evaluation to inform pricing and/or incorporate nontraditional sources of value and the views of diverse stakeholders. The changing role of economic evaluation in (formally or informally) assessing prices/values in four jurisdictions (UK, Australia, Germany and USA) is detailed and the authors propose a taxonomy of factors impacting the value of medical technology spanning clinical utility (effectiveness, safety/tolerability and quality of evidence), consumer demand (consumer preferences, process utility and unmet need), economic incentives (innovation, option value and market competition) and the societal perspective (social justice, social values and national interest). The authors suggest that multicriteria decision analysis methods grounded in hedonic-pricing theory can facilitate the valuing/pricing of medical technologies. The use of such an approach is hindered by a paucity of relevant educational opportunities, vested interests and aversion to placing prices/values on health.